Macro-Bending Loss of Single-Mode Fiber Beyond Its Operating Wavelength - Dwi Bayuwati; Tomi Budi Waluyo (Universitas Ahmad Dahlan, 2018)
A standard telecommunication-grade single-mode optical fiber is designed to have a low macro-bending loss in its entire operating wavelengths to comply with the ITU-T Recommendation G.652. In this paper, we described the potential use of such a fiber as an intensity-based sensor due to the macro-bending loss as an alternative to using a bending-sensitive fiber. We calculated the macro-bending loss of several single-mode optical fiber patchcords using the classical Marcuse equation at several wavelengths, and measured its transmission loss due to bending using an optical spectrum analyzer. For each type of fibers there is a wavelength with a significant macro-bending loss of the LP11 mode when the V-number of the fiber lies between 2.4 and 4, and that of the LP01 mode when the V-number of the fiber lies between 1 and 2.4. This work shows a thorough mathematical and experimental analysis for the posibility in using standard telecommunication fibers for intensity based-fiber sensor taking the benefit of bending loss phenomenon using commercial light sources.